2017
DOI: 10.1063/1.4977161
|View full text |Cite
|
Sign up to set email alerts
|

Dihadron production at LHC: BFKL predictions for cross sections and azimuthal correlations

Abstract: Abstract.A study of the inclusive production of a pair of hadrons (a "dihadron" system), having high transverse momenta and separated by a large interval of rapidity, is presented. This process has much in common with the widely discussed Mueller-Navelet jet production and can be also used to access the BFKL dynamics at proton colliders. Large contributions enhanced by logarithms of energy can be resummed in perturbation theory within the BFKL formalism in the next-to-leading logarithmic accuracy. The experime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Then, forward-hadron impact factors allowed us for a complete NLA study of the inclusive detection of two identified hadrons (composed of light quarks and well separated in rapidity) [65][66][67], and of the inclusive hadron-jet hadroproduction [68][69][70][71].…”
Section: Introductory Remarksmentioning
confidence: 99%
“…Then, forward-hadron impact factors allowed us for a complete NLA study of the inclusive detection of two identified hadrons (composed of light quarks and well separated in rapidity) [65][66][67], and of the inclusive hadron-jet hadroproduction [68][69][70][71].…”
Section: Introductory Remarksmentioning
confidence: 99%
“…[33,34] for a review): the diffractive leptoproduction of two light vector mesons [35][36][37][38], the total cross section of two highly-virtual photons [39], the inclusive hadropro-0123456789(). : V,-vol duction of two jets featuring large transverse momenta and well separated in rapidity (Mueller-Navelet channel [40]), for which several phenomenological studies have appeared so far [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], the inclusive detection of two light-charged hadrons [58][59][60], three-and four-jet hadroproduction [61][62][63][64][65][66][67][68][69], J/ -jet [70], hadron-jet [71][72][73][74], Drell-Yan-jet [75,76] and heavy-quark pair photo- [77,78] and hadroproduction [79].…”
Section: Introductionmentioning
confidence: 99%
“…We refer to Refs. [15][16][17][18][19][20] for similar studies. It is well known that fixed order calculations are unstable when the lower cut on the transverse momenta of both jets is the same, which is the situation encountered by the above CMS measurement [11].…”
Section: Results: Symmetric Configuration and Cms Datamentioning
confidence: 86%